The Infected Implant - Kienapfel, Heino.; K<U+00fc>hn, Klaus-Dieter. (Springer Berlin Heidelberg, 2009)
Musculosketal infections are potentially devastating for the patient, his family and the health care services, as they may lead to functional impairment, long lasting disability, or even permanent handicap. This problem may also have socioeconomic implications. Infection commonly results in prolonged use of antibiotics, multiple operations, complications, extended rehabilitation and long lasting follow-up visits with additional costs for the health care provider. The 2nd International Arthroplasty Symposium The Infected Implant" brought together international experts and will concentrate on infections: development, microbiology, diagnostics, statistics and therapy of the infected implant. Concerning microbiological diagnostics, a major challenge is the differentiation between septic and aseptic prosthesis loosening. Biofilm formation at low grade infections will therefore be one of our main topics at the event in 2008. Furthermore, the issue of antibiotic resistances, which is always a hot topic,will be discussed, based on new clinical and epidemiological data.These days, a number of options for the therapy of the infected implant are available. Lectures about the rational use of antibiotic medication and theapplication of antibiotic containing spacers will represent key topics of this meeting. The question whether revision surgery should be cemented or not will be another subject of the panel discussion, where clinicians of different countries worldwide will present their revision cases. A third part of the symposium will cover consequences and economical aspects of infected implants. The speakers will focus on the different European Arthroplasty Registers, but the issue of reimbursement practices within the EU will also be discussed.